1983
DOI: 10.1111/j.1365-2605.1983.tb00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high dose oral Kallikrein treatment in men with idiopathic subfertility: evaluation by means of in vitro penetration test of zona free hamster ova

Abstract: High dose oral Kallikrein treatment (600 U Padutine per day) was given to 10 infertile men with poor semen quality. After 3 months of this treatment no pregnancies occurred, and no significant changes in routine semen characteristics were observed. Moreover, the capacity of the spermatozoa to migrate in vitro and to penetrate zona free hamster ova remained unchanged after Kallikrein ingestion. It is concluded that Kallikrein treatment was ineffective in these men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1984
1984
2005
2005

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Some investigators claim that treating men with kallikrein improves their semen quality. Comhaire and Vermeulen [1983], however, have reported that kallikrein treatment of infertile men with poor semen quality neither improves semen quality drastically nor increases the hamster egg penetration rate. None of the ten men they treated impregnated their partners after 3 mo of the treatment.…”
Section: It Is Clear Frommentioning
confidence: 95%
“…Some investigators claim that treating men with kallikrein improves their semen quality. Comhaire and Vermeulen [1983], however, have reported that kallikrein treatment of infertile men with poor semen quality neither improves semen quality drastically nor increases the hamster egg penetration rate. None of the ten men they treated impregnated their partners after 3 mo of the treatment.…”
Section: It Is Clear Frommentioning
confidence: 95%
“…Depuis plusieurs annees, I'arginine [2,17] et la kallicreine [60] sont recommandees pour traiter les hommes atteints d'une oligozoospermie. Les pretendus effets favorables de ces complements alimentaires sur le traitement de patients atteints d'une oligozoospermie idiopathique ont ete mis en doute dans d'autres etudes [11,53].…”
Section: Arginine Et Kallicreineunclassified
“…Les prétendus eff ets favorables de ces suppléments en traitement de routine chez les patients ayant une oligozoospermie idiopathique ont été mis en doute dans d'autres essais (Pryor et al 1978 ;Comhaire et Vermeulen 1983 ;Glezerman et al1993 ;Keck et al 1994).…”
Section: Ii41547 Arginine Et Kallicréineunclassified